Manajemen Homestay: Membangun Inovasi Digital Melalui Sistem Informasi - I Gusti Ayu Putu Wita Indrayani; Made Uttari Pitanatri; Ni Luh Dita Priliani; Ni Putu Selina Venysia; Ni Luh Putu Dewi Trisna Yanti; Wayan Audina Mahesa Putri (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
This community service project highlights the role and impact of guest houses in Karangasem's tourism, with a specific focus on Robert Guest House. The primary goal of this initiative is to develop an information system that strengthens the guest house's presence and enhances the quality of services provided to guests. To achieve this, various research methods have been employed, including a SWOT analysis, online platform development, and the implementation of digital marketing strategies. The outcomes of this project include the launch of Google Business, an official website, and social media accounts designed to increase the visibility and accessibility of the guest house. These efforts are expected to attract more tourists, boost the income of the guest house owner, and offer guests a better and more satisfying stay experience. Consequently, this project not only strengthens the position of Robert Guest House within the local tourism industry but also contributes to the economic growth of Karangasem and enhances the appeal of the destination as an attractive tourist spot.